PERSON DEIXIS AND ITS CULTURAL IMPLICATIONS IN ENGLISH AND UZBEK TEXTS - Boltaqulova Gulnoza Farruxovna; Rabbimova Sitora Ravshan qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
ANNOTATION: This article examines person deixis in English and Uzbek writings through a cultural and pragmatic lens. Person deixis, encompassing pronouns and other references to individuals in conversation, significantly influences interpersonal relationships and conveys social hierarchy. The research analyzes the utilization of first, second, and third person deixis by English and Uzbek speakers across different textual settings, such as conversations, brief texts, and social media updates. Particular emphasis is placed on the cultural effects of person deixis, including strategies for politeness, levels of formality, and social distance. Comparative examination shows both resemblances and distinctions in how the two languages convey social relationships and cultural standards through person deixis. The results enhance comprehension of cross-cultural communication and pragmatic skills in multilingual settings